2020
DOI: 10.3390/antibiotics9090588
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and Virulence of Methicillin-Resistant Staphylococcus aureus from Human, Chicken and Environmental Samples within Live Bird Markets in Three Nigerian Cities

Abstract: Background: Methicillin-resistant Staphylococcus aureus (MRSA) has emerged as a major threat to public health. This study investigated the occurrence of MRSA in humans, chickens, chicken meat and environmental samples within poultry farms and live bird markets in southwestern Nigeria. Methods: MRSA were isolated using selective culture and tested for antimicrobial susceptibility by broth microdilution. Selected isolates were characterized by whole genome sequencing (WGS). From WGS data, spa, dru, multilocus se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 44 publications
(60 reference statements)
4
16
3
Order By: Relevance
“…All the isolates phenotypically multidrug-resistant (MDR), had an MAR index of ≥0.2, which suggests that the isolates originated from a source where antibiotics are used frequently [ 23 ]. The high rates of resistance observed towards the β-lactams, penicillins, tetracyclines and macrolides are consistent with the findings from previous studies in animals and animal products, including pigs and pork [ 10, 21, 22, 24 ], poultry [ 25 ], cattle [ 26 ], camels [ 27 ] and humans [ 11, 21, 25 ] in Nigeria. This high rate of resistance may not be coincidental, as we hypothesize that it is linked to the well-documented widespread, heavy and unregulated use of these agents in pig production across the country for prophylaxis and therapy [ 28 ].…”
Section: Discussionsupporting
confidence: 89%
“…All the isolates phenotypically multidrug-resistant (MDR), had an MAR index of ≥0.2, which suggests that the isolates originated from a source where antibiotics are used frequently [ 23 ]. The high rates of resistance observed towards the β-lactams, penicillins, tetracyclines and macrolides are consistent with the findings from previous studies in animals and animal products, including pigs and pork [ 10, 21, 22, 24 ], poultry [ 25 ], cattle [ 26 ], camels [ 27 ] and humans [ 11, 21, 25 ] in Nigeria. This high rate of resistance may not be coincidental, as we hypothesize that it is linked to the well-documented widespread, heavy and unregulated use of these agents in pig production across the country for prophylaxis and therapy [ 28 ].…”
Section: Discussionsupporting
confidence: 89%
“…PVL-positive t590-ST1-V [5C2] was documented from nasal samples both in hospitalized patients and health care workers (HCWs) in São Tomé and Príncipe ( Conceição et al, 2015a , b ). Another PVL-positive lineage: t657-ST772-V [5C2] (Bengal Bay Clone), was detected from human nasal samples in the community setting in Nigeria ( Ogundipe et al, 2020 ). Moreover, PVL-negative t127-ST1-IV [2B] was described in a nasal sample of a non-hospitalized individual in Morocco ( Mourabit et al, 2017 ), while it’s variant (t127-ST1-V [5C2]) was identified from non-human specimens (milk products) in Uganda ( Asiimwe et al, 2017b ).…”
Section: Resultsmentioning
confidence: 99%
“…The PVL-negative ST8-V/VII (largely t1476) was the major clone in the DRC ( Lebughe et al, 2017 ; Vandendriessche et al, 2017 ), and Angola ( Aires-de-Sousa et al, 2018 ). Two countries, i.e., Morocco ( Mourabit et al, 2017 ) and Nigeria ( Ogundipe et al, 2020 ), described ST8-V [5C2] with different spa types (t2231, t2658, and t12236) in non-clinical settings. The t456-ST8-I [1B] was only identified in South Africa ( Mahomed et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the Nigerian’ poultry value chain, live bird markets (LBMs) are essential to the farmers for the preferential sales and marketing of poultry and poultry products for human consumption [ 1 ]. The LBMs are typically in urban, peri-urban, and rural settings and typified by permanently placed pen-like structures in which the chickens can be temporarily housed until they are sold [ 2 ]. The LBMs bring together a variety of multi-farmed, multi-sourced, and multi-aged poultry species to meet the preferences of various customers [ 3 ].…”
Section: Introductionmentioning
confidence: 99%